Efektivitas Penggunaan Media Sosial Instagram FKOMINFO bagi Calon Mahasiswa Baru - Hermawan, Tsanya Firgy (Intitut Agama Islam Nasional Laa Roiba Bogor, 2025)
The rapidly developing internet technology has significantly impacted daily life, particularly through social media. Social media serves as a platform that allows individuals to interact with one another online, one of which is Instagram. Instagram is a popular photo-sharing application that has various interests, such as following trends, socializing, and promoting activities. FKOMINFO UNIGA Instagram account @fkominfo.universitasgarut is a communication platform that provides information to prospective students. This study aims to determine the effectiveness of the Instagram account @fkominfo.universitasgarut for new prospective students. This research employs a qualitative method that focuses on a deep understanding of phenomena through interviews and documentation, utilizing the Uses and Gratifications theory to comprehend how individuals choose and use the FKOMINFO Instagram social media to meet their needs and desires as prospective new students. The results indicate that Instagram @fkominfo.universitasgarut effectively serves as a primary source of information for new prospective students, providing a clear understanding of the registration process and study programs through engaging visual content. Additionally, this platform creates positive emotional engagement, facilitates constructive social interactions, and offers easy access to information for new prospective students.